An electromagnetic sensor for the autonomous running of visually impaired and blind athletes (Part I: The fixed infrastructure) - Pieralisi, M.; Di Mattia, V.; Petrini, V.; De Leo, A.; Manfredi, G.; Russo, P.; Scalise, L.; Cerri, G. (Sensors, 2017)
Sport is one of the best ways to promote the social integration of people affected by physical disability, because it helps them to increase their self-esteem by facing difficulties and overcoming their disabilities. Nowadays, a large number of sports can be easily played by visually impaired and blind athletes without any special supports, but, there are some disciplines that require the presence of a sighted guide. In this work, the attention will be focused on marathons, during which athletes with visual disorders have to be linked to the sighted guide by means of a non-stretchable elbow tether, with an evident reduction of their performance and autonomy. In this context, this paper presents a fixed electromagnetic infrastructure to equip a standard running racetrack in order to help a blind athlete to safely run without the presence of a sighted guide. The athlete runs inside an invisible hallway, just wearing a light and a comfortable sensor unit. The patented system has been homemade, designed, realized and finally tested by a blind Paralympic marathon champion with encouraging results and interesting suggestions for technical improvements. In this paper (Part I), the transmitting unit, whose main task is to generate the two magnetic fields that delimit the safe hallway, is presented and discussed.